2014
DOI: 10.1155/2014/903798
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Stasis‐Stagnation Constitution and Peripheral Arterial Disease in Patients with Type 2 Diabetes

Abstract: Objectives. In traditional Chinese medicine, Yu-Zhi (YZ, indicating stasis and stagnation) constitution describes a body that tends to express abnormal circulatory conditions. This study identified the linkage between YZ constitution and peripheral arterial disease (PAD) in patients with type 2 diabetes. Methods. Patients over 20 years of age who had had type 2 diabetes for 5 years or longer were recruited. PAD was diagnosed if the ankle-brachial index score was ≤0.9 in either leg. Level of YZ constitution was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
4
21
0
Order By: Relevance
“…Recorded results revealed that the total cholesterol, triglyceride and LDL are increased significantly (p≤0.05) in the T2DM patients while HDL is significantly (p≤0.05) decreased when compared with the controls. These results agreed with Agrawal et al [26] and Huang et al [27] .The probable reason of the elevating concentrations of serum cholesterol may be referred to many factors such as obesity, increase calorie intake and lack of muscular exercise or suppression of cholesterol catabolism [28].…”
Section: Discussionsupporting
confidence: 92%
“…Recorded results revealed that the total cholesterol, triglyceride and LDL are increased significantly (p≤0.05) in the T2DM patients while HDL is significantly (p≤0.05) decreased when compared with the controls. These results agreed with Agrawal et al [26] and Huang et al [27] .The probable reason of the elevating concentrations of serum cholesterol may be referred to many factors such as obesity, increase calorie intake and lack of muscular exercise or suppression of cholesterol catabolism [28].…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the lipids (TC, TG, LDL-C, VLDL-C) of the diabetics were higher than that of the controls and is similar as shown by Masum et al, and Huang et al 20,21 The absolute LDL-C concentration in present study is not altered significantly, as it does not directly reflect the increased TG and VLDL-C levels. 22 Our study shows high TC in 74%, high TG in 90%, high LDL-C in 30% and Low HDL-C in 42% in diabetic cases, while most dyslipidemic combination was high TC and high TG 72% cases.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the menopausal symptoms of heart discomfort, physical/mental exhaustion, and sleeping problems could be associated with this type of constitution. According to the published literature, phlegm and blood stasis syndrome constitute the main pathological components of hyperlipidemia [28], coronary heart disease [29], and diabetic peripheral arterial disease [6]. The incidence of cardiovascular disease increases considerably after perimenopause.…”
Section: Discussionmentioning
confidence: 99%
“…Data from 4 diagnostic methods are analyzed according to TCM theories to form a constitutional diagnosis. Past studies have revealed that the BC is greatly influenced by age, chronic diseases [5,6,7], psychological symptoms, and lifestyle [8]. Constitution identification is the basis of TCM syndrome differentiation.…”
Section: Introductionmentioning
confidence: 99%